2020
DOI: 10.1152/ajpendo.00220.2020
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylation of fetal liver IGFBP-1 precedes slowing of fetal growth in nutrient-restricted baboons and may be a mechanism underlying IUGR

Abstract: In cultured fetal liver cells, IGFBP-1 hyperphosphorylation in response to hypoxia and amino acid deprivation is mediated by inhibition of mechanistic target of rapamycin (mTOR) and activation of amino acid response (AAR) signalling and casein kinase CK2. We hypothesized that fetal liver mTOR inhibition, activation of AAR and CK2, and IGFBP-1 hyperphosphorylation occur prior to development of intrauterine growth restriction (IUGR). Pregnant baboons were fed a Control (C) or a Maternal Nutrient Restriction (MNR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…However, we have previously demonstrated that increased IGFBP-1 phosphorylation leads to inhibition of IGF-1-induced IGF-IR autophosphorylation functionally, irrespective of the kinase involved. 8,13,25,28,29 We therefore propose that the activation of decidual PKA as reported in the current study promotes interaction and phosphorylation of decidual IGFBP-1, which could lead to decreased IGF-1 bioavailability at the maternal–fetal interface early in pregnancy prior to development of IUGR.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, we have previously demonstrated that increased IGFBP-1 phosphorylation leads to inhibition of IGF-1-induced IGF-IR autophosphorylation functionally, irrespective of the kinase involved. 8,13,25,28,29 We therefore propose that the activation of decidual PKA as reported in the current study promotes interaction and phosphorylation of decidual IGFBP-1, which could lead to decreased IGF-1 bioavailability at the maternal–fetal interface early in pregnancy prior to development of IUGR.…”
Section: Discussionsupporting
confidence: 60%
“…By feeding pregnant baboons a calorie-restricted diet (70% of controls), 26 our non-human primate model of maternal nutrient reduction (MNR) results in IUGR close to term. Although we have reported increased IGFBP-1 expression and phosphorylation in the liver of MNR baboon fetuses, 8,27,28 the expression of decidual PKA and its association with IGFBP-1 in the baboon IUGR placenta have not been established.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In-solution digestion of the IP samples for PRM-MS analyses of IGFBP-1 phosphopeptides were performed, as described previously [ 66 ], to analyze the site-specific phosphorylation of IGFBP-1. IGFBP-1 co-immunoprecipitated CK2 and PKC.…”
Section: Methodsmentioning
confidence: 99%
“…Peptide digests were desalted with C18-ZipTip, dried in a Thermo SpeedVac, and then samples were loaded onto a Thermo Easy-Spray analytical column with an Easy-nLC 1000 chromatography pump. A Q-Exactive hybrid quadrupole-Orbitrap mass spectrometer coupled to an Easy-nLC 1000 system (ThermoFisher) was used to collect mass spectra as described [ 66 ]. Internal peptide for IGFBP-1 (NH2-ALPGEQQPLHALTR-COOH), CK2 (NH2-WERFVHSENQHLVSPEAL-COOH), were used to normalize respective phosphopeptide data against total protein abundance.…”
Section: Methodsmentioning
confidence: 99%